The Role of Dysbiosis in Critically Ill Patients With COVID-19 and Acute Respiratory Distress Syndrome - Denise Battaglini; Denise Battaglini; Chiara Robba; Chiara Robba; Andrea Fedele; Sebastian Trancǎ; Sebastian Trancǎ; Samir Giuseppe Sukkar; Vincenzo Di Pilato; Matteo Bassetti; Matteo Bassetti; Daniele Roberto Giacobbe; et al. (Frontiers in Medicine, 2021)
In late December 2019, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) quickly spread worldwide, and the syndrome it causes, coronavirus disease 2019 (COVID-19), has reached pandemic proportions. Around 30% of patients with COVID-19 experience severe respiratory distress and are admitted to the intensive care unit for comprehensive critical care. Patients with COVID-19 often present an enhanced immune response with a hyperinflammatory state characterized by a “cytokine storm,” which may reflect changes in the microbiota composition. Moreover, the evolution to acute respiratory distress syndrome (ARDS) may increase the severity of COVID-19 and related dysbiosis. During critical illness, the multitude of therapies administered, including antibiotics, sedatives, analgesics, body position, invasive mechanical ventilation, and nutritional support, may enhance the inflammatory response and alter the balance of patients' microbiota. This status of dysbiosis may lead to hyper vulnerability in patients and an inappropriate response to critical circumstances. In this context, the aim of our narrative review is to provide an overview of possible interaction between patients' microbiota dysbiosis and clinical status of severe COVID-19 with ARDS, taking into consideration the characteristic hyperinflammatory state of this condition, respiratory distress, and provide an overview on possible nutritional strategies for critically ill patients with COVID-19-ARDS.